Representing beasts in early Medieval England and Scandinavia - Bintley, Michael D. J.; Williams, Thomas J. T. (The Boydell Press, 2015)
For people in the early Middle Ages, the earth, air, water and ether teemed with other beings. Some of these were sentient creatures that swam, flew, slithered or stalked through the same environmentsinhabited by their human contemporaries. Others were objects that a modern beholder would be unlikely to think of as living things, but could yet be considered to possess a vitality that rendered them potent. Still others were things half glimpsed on a dark night or seen only in the mind's eye; strange beasts that haunted dreams and visions or inhabited exotic lands beyond the compass of everydayknowledge. This book discusses the various ways in which the early English and Scandinavians thought about and represented these other inhabitants of their world, and considers the multi-facetednature of the relationship between people and beasts. Drawing on the evidence of material culture, art, language, literature, place-names and landscapes, the studies presented here reveal a world where the boundaries between humans, animals, monsters and objects were blurred and often permeable, and where to represent the bestial could be to hold a mirror to the self. Michael Bintley is Senior Lecturer in Medieval Literature at Canterbury Christ Church University; Thomas Williams is a doctoral researcher at UCL's Institute of Archaeology. Contributors: Noel Adams, John Baker, Michael D. J. Bintley, Sue Brunning, László Sándor Chardonnens, Della Hooke, Eric Lacey, Richard North, Marijane Osborn, Victoria Symons, Thomas J. Williams
Title from publisher's bibliographic system (viewed on 11 Jun 2021)
Keywords: Great Britain / History / Anglo-Saxon period, 449-1066; Scandinavia / Civilization / To 1500; England--Civilization--To 1500